2021
DOI: 10.3390/nu13051539
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Iron Overload in Obesity and Implications in Metabolic Health

Abstract: Excessive adiposity is associated with several metabolic perturbations including disturbances in iron homeostasis. Increased systemic inflammation in obesity stimulates expression of the iron regulatory hormone hepcidin, which can result in a maldistribution of bodily iron, which may be implicated in metabolic dysfunction. This study aimed to investigate the effect of adiposity and any associated inflammation on iron homeostasis and the potential implications of dysregulated iron metabolism on metabolic health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…In particular, obese patients with combined chronic inflammatory conditions are more susceptible to hypoferritinemia (serum ferritin deficiency), which can be considered to be related to iron deficiency caused by the inflammatory response (Yanoff et al 2007 ). Serum ferritin levels are positively correlated with serum insulin and HOMA-IR values (Moore Heslin et al 2021 ), and there is evidence of an association between serum iron levels and metabolic syndrome (Sachinidis et al 2020 ). Lowering plasma ferritin was proved to improve NAFLD in obese patients, suggesting that consideration of iron status is imperative in the treatment of obesity-related metabolic dysfunction (Moore Heslin et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, obese patients with combined chronic inflammatory conditions are more susceptible to hypoferritinemia (serum ferritin deficiency), which can be considered to be related to iron deficiency caused by the inflammatory response (Yanoff et al 2007 ). Serum ferritin levels are positively correlated with serum insulin and HOMA-IR values (Moore Heslin et al 2021 ), and there is evidence of an association between serum iron levels and metabolic syndrome (Sachinidis et al 2020 ). Lowering plasma ferritin was proved to improve NAFLD in obese patients, suggesting that consideration of iron status is imperative in the treatment of obesity-related metabolic dysfunction (Moore Heslin et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Serum ferritin levels are positively correlated with serum insulin and HOMA-IR values (Moore Heslin et al 2021 ), and there is evidence of an association between serum iron levels and metabolic syndrome (Sachinidis et al 2020 ). Lowering plasma ferritin was proved to improve NAFLD in obese patients, suggesting that consideration of iron status is imperative in the treatment of obesity-related metabolic dysfunction (Moore Heslin et al 2021 ). Here, we summarize the pathophysiological mechanisms of iron action in obesity and its related metabolic diseases to provide new perspectives for the prevention and treatment of obesity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, lesser degrees of iron overload are required to raise TSAT levels. This in general makes increased TSAT a more sensitive marker than ferritin ( 40 ). Moreover, in the current article, we review the existing literature about the relationship between iron status and obesity without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the current article, we review the existing literature about the relationship between iron status and obesity without diabetes. An analysis based on a subsample from the cross-sectional Irish National Adult Nutrition Survey (2008–2010) by Heslin et al has indicated that excessive body fat was significantly associated with increased serum hepcidin and ferritin and an increased prevalence of severe risk of iron overload ( 41 ). Hepcidin inhibits dietary absorption in the duodenum, the release of recycled iron from macrophages, and the exit of stored iron from hepatocytes by downregulation of ferroportin ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation